Fabrication and evaluation of thermosensitive chitosan/collagen/α, β-glycerophosphate hydrogels for tissue regeneration. (1st July 2017) - Dang, Qifeng; Liu, Kai; Zhang, Zhenzhen; Liu, Chengsheng; Liu, Xi; Xin, Ying; Cheng, Xiaoyu; Xu, Tao; Cha, Dongsu; Fan, Bing
Highlights: CS-ASC-HGs were successfully prepared and had excellent thermosensitivity. CS-ASC-HGs possessed 3D porous architectures containing fibrous ASC. CS-ASC-HGs had better pH stability and biocompatibility than pure CS-HG. CS-ASC-HGs could serve as 3D cell culture matrices for L929. Abstract: Thermosensitive hydrogels whose physiological properties are similar to extracellular matrix have been extensively used for tissue regeneration. Polysaccharides and proteins, as biocompatible substrates similar to bio-macromolecules that could be recognized by human body, are two preferred polymers for fabrication of such hydrogels. A series of novel thermosensitive hydrogels (CS-ASC-HGs) containing chitosan (CS) and acid-soluble collagen (ASC) were thus prepared, in the presence of α, β-glycerophosphate, to mimic extracellular microenvironment for tissue regeneration. Rheological measurements demonstrated excellent thermosensitivity. FT-IR and SEM indicated CS-ASC-HGs possessed 3D porous architectures with fibrous ASC, and the molecular structure of ASC was well-maintained in hydrogels. Hemolysis, acute toxicity, and cytotoxicity tests suggested CS-ASC-HGs were of good biocompatibility. CS-ASC-HGs were able to support the survival and proliferation of L929 cells encapsulated in them. Moreover, CS-ASC-HGs had better pH stability and biocompatibility than pure CS hydrogel. These results suggested that CS-ASC-HGs could serve as promising scaffolds for tissue regeneration.